Deferasirox improved iron homeostasis and hematopoiesis in ovariectomized rats with iron accumulation - Niloofar Honari; Mahtab Sayadi; Seyed Mehdi Sajjadi; Somayeh Solhjoo; Gholamreza Anani Sarab (Scientific Reports)
Abstract Menopause is a natural biological aging process characterized by the loss of ovarian follicular function and decrease estrogen levels. These hormonal fluctuations are associated with increased iron levels, which ultimately lead to iron accumulation. This study aims to investigate the effects of Deferasirox on iron homeostasis and hematopoiesis in ovariectomized rats with iron accumulation. Sixty-four female Wistar rats were divided into eight groups and underwent ovariectomy surgery to simulate menopause. Iron accumulation was induced through the injection of ammonium ferric citrate. Deferasirox was administered at doses of 50 mg/kg and 100 mg/kg. Hematological parameters, iron profile, antioxidant markers, oxidative stress indicators, histopathological evaluation of uterine, bone, bone marrow, liver, and spleen tissues, flow cytometric analysis of hematopoietic CD markers, and relative expression of Hamp, Pu.1, Gata1, and Gdf11 genes were analyzed. Deferasirox treatment improved histopathological changes in the uterine tissue of ovariectomized rats with iron accumulation, increased the number of white blood cells, and reduced serum iron levels, TIBC, ferritin, and transferrin saturation percentage. It also increased serum antioxidant capacity and reduced oxidative stress markers. Deferasirox had a positive effect on femur bone, hematopoietic cell count, volume of hematopoietic and adipose tissues in bone marrow, extramedullary hematopoiesis in the liver and spleen, and influenced the relative expression of Hamp, Pu.1, Gata1, and Gdf11 genes related to hematopoiesis and iron metabolism. In conclusion, Deferasirox effectively manages iron homeostasis and hematopoiesis in ovariectomized rats with iron accumulation and suppresses oxidative stress.